User-identified gel characteristics: a qualitative exploration of perceived product efficacy of topical vaginal microbicides. - Morrow, Kathleen M; Underhill, Kristen; Van Den Berg, Jacob J; Vargas, Sara; Rosen, Rochelle K; Katz, David F (Archives of sexual behavior, 2014)
Research has demonstrated that certain vaginal gel products--microbicides containing antiretroviral drugs--may reduce HIV infection risk among women. But for vaginal gels to avert HIV and other sexually transmitted infections (STIs), at-risk women must be willing to use them as directed. These products must therefore be "acceptable" to women and an important component of acceptability is users' perception that the product will work to prevent infection. We sought to understand how women's perceptions of vaginal gel properties may shape their understanding of product efficacy for HIV and STI prevention. Sixteen women completed two in-depth qualitative interviews (k = 32) to identify the range and types of sensory perceptions they experienced when using two vaginal gels. We identified emergent themes and linkages between users' sensory perceptions and their beliefs about product efficacy. Users' predictions about product efficacy for preventing infection corresponded to measurable physical properties, including gel volume, location in the vagina, coating behavior, sensation of the gel in the vagina, leakage, and gel changes during coital acts. Although the women described similar sensory experiences (e.g., gel leaked from the vagina), they interpreted these experiences to have varying implications for product efficacy (e.g., leakage was predicted to increase or decrease efficacy). To improve microbicide acceptability, gel developers should investigate and deliberately incorporate properties that influence users' perceptions of efficacy. When a microbicide is approved for use, providers should educate users to anticipate and understand their sensory experiences; improving users' experience can maximize adherence and product effectiveness.
Keywords: Administration, Intravaginal; Adolescent; Adult; Anti-Infective Agents, Local; Consumer Satisfaction; Female; HIV Infections; Humans; Middle Aged; Patient Acceptance of Health Care; Sexually Transmitted Diseases; Vaginal Creams, Foams, and Jellies; Vaginal Diseases; Young Adult